The Influence of Locus of Control on Organizational Commitment Among Members of the Ar-Risalah Campus Da’wah Organization at UIN Ar-Raniry Banda Aceh - Syarifuddin, Rahima Diagra; Julianto, Julianto; Nova, Vera (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Organizational commitment refers to an individual’s desire to remain within an organization. Locus of control is considered to influence an individual’s level of organizational commitment. Locus of control is divided into two types: internal locus of control and external locus of control. This study aims to examine the influence of locus of control on organizational commitment among members of the Ar-Risalah Campus Da’wah Organization at UIN Ar-Raniry Banda Aceh. The research employed a quantitative approach, with data analysis conducted using multiple linear regression, and the saturated sampling technique was applied for participant selection. The instruments used in this study were the Locus of Control Scale and the Organizational Commitment Scale. The results of the hypothesis testing indicated that the external locus of control dimension had a significant influence on organizational commitment among members of the Ar-Risalah Campus Da’wah Organization at UIN Ar-Raniry Banda Aceh, with a significance value of 0.024 (p < 0.05). This finding means that the external locus of control dimension significantly affects organizational commitment.